Coagulation, inflammation, and CD46 transgene expression in neonatal porcine islet xenotransplantation. (22nd February 2021) - Song, Mingqing; Fitch, Zachary W.; Samy, Kannan P.; Martin, Benjamin M.; Gao, Qimeng; Patrick Davis, Robert; Leopardi, Francis V.; Huffman, Niki; Schmitz, Robin; Devi, Gayathri R.; Collins, Bradley H.; Kirk, Allan D.
Abstract: Background: Thrombosis is a known consequence of intraportal islet transplantation, particularly for xenogeneic islets. To define the origins of thrombosis after islet xenotransplantation and relate it to early inflammation, we examined porcine islets transplanted into non‐human primates using a dual‐transplant model to directly compare islet characteristics. Methods: α1, 3‐Galactosyltransferase gene‐knockout (GTKO) islets with and without expression of the human complement regulatory transgene CD46 (hCD46) were studied. Biologically inert polyethylene microspheres were used to examine the generic pro‐thrombotic effects of particle embolization. Immunohistochemistry was performed 1 and 24 hours after transplantation. Results: Xeno‐islet transplantation activated both extrinsic and intrinsic coagulation pathways. The intrinsic pathway was also initiated by microsphere embolization, while extrinsic pathway tissue factor (TF) and platelet aggregation were more specific to engrafted islets. hCD46 expression significantly reduced TF, platelet, fibrin, and factor XIIIa accumulation in and around islets but did not alter intrinsic factor activation. Layers of TF + cells emerged around islets within 24 hours, particularly co‐localized with vimentin, and identified as CD3+ and CD68+ cells inflammatory cells. Conclusions: These findings detail the origins of thrombosis following islet xenotransplantation, relate it to early immune activation, and suggest a role for transgenic hCD46 expression in its mitigation. Layers of TF‐positive inflammatory cells and fibroblasts around islets at 24 hours may have important roles in the progressive events of thrombosis, inflammatory cell recruitment, rejection, and the ultimate outcome of transplanted grafts. These suggest that the strategies targeting these elements could yield more progress toward successful xenogeneic islet engraftment and survival.